In‐hospital ventricular arrhythmia in heart failure patients: 7 year follow‐up of the multi‐centric HEARTS registry. (21st November 2019) - Alenazy, Basel; Tharkar, Shabana; Kashour, Tarek; Alhabib, Khalid Faiz; Alfaleh, Hussam; Hersi, Ahmad
Abstract: Aims: The aim of this study was to determine the incidence, predictors, and short‐term and long‐term outcomes associated with in‐hospital sustained ventricular tachycardia (VT) and ventricular fibrillation (VF) collectively termed ventricular arrhythmia (VA) in the heart failure (HF) patients. Methods and results: The HEart function Assessment Registry Trial in Saudi Arabia (HEARTS registry) is a prospective national registry of patients with chronic HF from18 tertiary care hospitals across Saudi Arabia. Diagnosis of HF was in accordance with American Heart Association/European Society of Cardiology definition criteria. The registry had enrolled 2610 HF patients during the 14 month recruitment period between October 2009 and December 2010. Occurrence of in‐hospital cardiac events, prognosis, and outcome were monitored during the 7 year follow‐up period. The incidence of in‐hospital VA in HF was 4.2%. VA was more common among men, and mean age was lesser than non‐VA patients (58.5 ± 16: 61.5 ± 15 years; P = 0.042). Smoking and family history of cardiomyopathy were significant risk factors of VA. Previous history of arrhythmia, ST elevated myocardial infarction, infections, and hypotension remained significant predictors of in‐hospital VA associated with three to seven times more risk. Patients with VA had higher rates of in‐hospital events like recurrent HF, haemodialysis, shock, sepsis, major bleeding, intra‐aortic balloon pump, and stroke compared with those without VA, all being highly significant ( P < 0.001). After adjustment for age, gender, and co‐morbidities, in‐hospital VA increased the risk of cardiogenic shock by 24 times, dialysis and major bleeding by 10 times, and recurrent congestive HF and pacing by five times. Survival analysis showed that all‐cause mortality was significantly higher in the VA patients ( P < 0.001). Presence of VA increased in‐hospital and 1 month mortality to 23 and 17 times, respectively. Conclusions: Lower mean age of VA complicated HF patients is a matter of concern in the Saudi population. HF associated with VA increased in‐hospital events and all‐cause mortality indicating poor prognosis and survival. These findings enable risk stratification and reflect on the importance of early recognition of the clinical markers and predictors of VA prompting immediate management.